The Detection of Malingered Amnesia: An Approach Involving Multiple Strategies in a Mock Crime - Zago, Stefano; Piacquadio, Emanuela; Monaro, Merylin; Orrù, Graziella; Sampaolo, Erika; Difonzo, Teresa; Toncini, Andrea; Heinzl, Eugenio (Frontiers in Psychiatry, 2019)
The nature of amnesia in the context of crime has been the subject of a prolonged debate. It is not uncommon that after committing a violent crime, the offender either does not have any memory of the event or recalls it with some gaps in its recollection. A number of studies have been conducted in order to differentiate between simulated and genuine amnesia. The recognition of probable malingering requires several inferential methods. For instance, it typically involves the defendant’s medical records, self-reports, the observed behaviour, and the results of a comprehensive neuropsychological examination. In addition, a variety of procedures that may detect very specific malingered amnesia in crime have been developed. In this paper, we investigated the efficacy of three techniques, facial thermography, kinematic analysis and symptom validity testing in detecting malingering of amnesia in crime. Participants were randomly assigned to two different experimental conditions: a group was instructed to simulate an amnesia after a mock homicide, a second group was simply asked to behave honestly after committing the mock homicide. The outcomes show that kinematic analysis and symptom validity testing achieve significant accuracy in detecting feigned amnesia, while thermal imaging do not provide converging evidence. Results are encouraging and may provide a first step towards the application of these procedures in a multimethod approach on crime-specific cases of amnesia.